The pivotal role of CXCR7 in stabilization of the pulmonary epithelial barrier in acute pulmonary inflammation - Ngamsri, Kristian-Christos; Mueller, Anika; Boesmueller, Hans; Gamper-Tsigaras, Jutta; Reutershan, Jörg; Konrad, Franziska M. (Journal of Immunology, 2017)
Acute pulmonary inflammation is still a frightening complication in intensive care units and has a high mortality. Specific treatment is not available, and many details of the pathomechanism remain unclear. The recently discovered chemokine receptor CXCR7 and its ligand stromal cell-derived factor (SDF)-1 are known to be involved in inflammation. We chose to investigate the detailed role of CXCR7 in a murine model of LPS inhalation. Inflammation increased pulmonary expression of CXCR7, and the receptor was predominantly expressed on pulmonary epithelium and on polymorphonuclear neutrophil (PMNs) after transepithelial migration into the alveolar space. Specific inhibition of CXCR7 reduced transepithelial PMN migration by affecting the expression of adhesion molecules. CXCR7 antagonism reduced the most potent PMN chemoattractants CXCL1 and CXCL2/3. After inhibiting CXCR7, NF-kB phosphorylation was reduced in lungs of mice, tight junction formation increased, and protein concentration in the bronchoalveolar lavage diminished, showing the impact of CXCR7 on stabilizing microvascular permeability. In vitro studies with human cells confirmed the pivotal role of CXCR7 in pulmonary epithelium. Immunofluorescence of human lungs confirmed our in vivo data and showed an increase of the expression of CXCR7 in pulmonary epithelium. Highlighting the clinical potential of CXCR7 antagonism, nebulization of the agent before and after the inflammation showed impressive anti-inflammatory effects. Additional CXCR7 inhibition potentiated the effect of SDF-1 antagonism, most probably by downregulating SDF-1 and the second receptor of the chemokine (CXCR4) expression. In conclusion, our data identified the pivotal role of the receptor CXCR7 in pulmonary inflammation with a predominant effect on the pulmonary epithelium and PMNs.
CRIS-Team Scopus Importer:2022-11-17